Investigating the role of Arabic language in sustaining socio-cultural identity and family values in Emirati society - Zakarneh, Bilal; Mahmoud, Diana Amin Mohammad (Frontiers in Sociology, 2025)
Language is a critical social and cultural identity component, further affecting family values and cohesion. Particularly, the importance of the Arabic language (UAE) cannot be overstated due to its distinct role in positioning the United Arab Emirates as a culturally distinct society. Considering the importance of the Arabic language, this study also examined its role and effect on socio-cultural identity and family values in Emirati society. Based on the proposition of Cultural Transmission Theory, this study gathered data from 200 young individuals currently residing in Ajman, UAE. Results revealed a positive effect of the Arabic language on socio-cultural identity, implying that it helps recognize local values and social participation and helps with the significance of social laws. The effect of the Arabic language on family values also remained significant, suggesting that it improves family relations, helps understand values and a sense of respect, and strengthens relationships with ancestral heritage. Overall, these results indicated the Arabic language's strong, sportive role in enhancing the sense of commitment and encouraging humility in society. These results also showed that the role of the Arabic language in promoting a sense of unity and social stability further leads to improved social participation. Thus, the role of the Arabic language is acknowledged and highlighted, further emphasizing the role of language as a source of communication and socio-cultural cohesion. Finally, study implications and limitations are discussed.